TINJAUAN POLITIK EKONOMI TERHADAP JEJARING RANTAI BISNIS TRADISIONAL MINYAK BUMI DI DESA SUNGAI ANGIT KECAMATAN BABAT TOMAN KABUPATEN MUSI BANYUASIN - Rhy, Rahayuni; Zalpa, Yulion; Wati, Reni Rentika (Jurnal Studi Ilmu Politik, 2024)
This research discusses the Political Economic Review of the Traditional Petroleum Business Chain Network in Babat Toman District, Musi Banyuasin Regency. The background of this research is that Babat Toman District is an area that has abundant potential oil reserves but illegal mining activities thrive on the assumption that management is not managed properly. This research uses a research method with a descriptive qualitative approach. The data in this research was obtained through direct observation and interviews with illegal miners and communities around the mining location. This research aims to find out how the network of actors in the petroleum business operates in the drilling process in the region. The theory used in this research is actor network theory which was initiated by Bruno Latour. The research results show that there are two main categories of petroleum mining in Sungai Angit Village, namely mining in old wells which is officially regulated and traditional mining which is often illegal. The oil mining actor network in Sungai Angit Village involves various actors, including authorities such as the government, mining companies, capital owners, land owners and miners. The interactions between these actors form a complex network in oil mining and processing activities. The process of processing old well oil involves various tools and collaboration between the community, organizations such as KMK, and companies such as PT. PBSA and PT Petro Muba. Even though it is traditional, the management and tools used have been improved to achieve optimal efficiency.